To solve the quadratic equation \((x + 36)^2 - 38 = 251\), we can follow these steps:
-
First, isolate the squared term: \[ (x + 36)^2 - 38 = 251 \] Add 38 to both sides: \[ (x + 36)^2 = 251 + 38 \] \[ (x + 36)^2 = 289 \]
-
Now, take the square root of both sides: \[ x + 36 = \pm \sqrt{289} \] The square root of 289 is 17, so: \[ x + 36 = 17 \quad \text{or} \quad x + 36 = -17 \]
-
Solve for \(x\) in both cases:
-
For \(x + 36 = 17\): \[ x = 17 - 36 \] \[ x = -19 \]
-
For \(x + 36 = -17\): \[ x = -17 - 36 \] \[ x = -53 \]
-
-
Therefore, the solutions to the equation are: \[ x = -19 \quad \text{and} \quad x = -53 \]
The solution set is: \[ {-19, -53} \]
So the correct response is: \({-19, -53}\)